ANALISIS BIBLIOMETRIK TREN PENELITIAN PADA PENERAPAN PAJAK KARBON MENGGUNAKAN VOSVIEWER - Richi Guali Padang; Rachmat Agus Santoso; Fitriana Fitriana (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the trend of research on carbon tax, focusing on article identification including the year of publication, the countries that produce the most articles, the articles with the most citations and related topics. This study uses bibliometric analysis with VOSviewer software based on Scopus data, covering 206 articles published from 2015-2025. Data was collected using the keyword “Carbon Tax” to be analyzed for identification. The results found that the number of publications on carbon tax fluctuated each year, with 2024 being the most published year with 37 articles. China and the United States lead in the number of articles and citations, followed by India and other countries. The article